2021
DOI: 10.1097/yco.0000000000000723
|View full text |Cite
|
Sign up to set email alerts
|

Who complies with coronavirus disease 2019 precautions and who does not?

Abstract: Purpose of review Severe acute respiratory syndrome (SARS)–coronavirus disease 2019 (COVID-19) virus imposes a higher risk of complications and mortality among people with mental disorders. Until widely available vaccines, adherence to preventive behaviours remains the most crucial tool to prevent SARS/COVID-19 virus transmission. Our review focuses on the determinants of adherence behaviours. Recent findings Adherence behaviours include the use of a face mask and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 61 publications
5
16
1
Order By: Relevance
“…Previous studies also supported the gender disparities in handwashing behaviour and knowledge regarding personal hygienic behaviours [ 25 , 26 ]. Our results regarding the gendered preventive behaviours are in accordance with other studies from different countries that documented gender disparities in adherence behaviours (see for a brief review [ 27 ]. However, further research is necessary to disentangle the multiple behavioural mechanisms explaining why males seem to be more vulnerable to respiratory infections.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies also supported the gender disparities in handwashing behaviour and knowledge regarding personal hygienic behaviours [ 25 , 26 ]. Our results regarding the gendered preventive behaviours are in accordance with other studies from different countries that documented gender disparities in adherence behaviours (see for a brief review [ 27 ]. However, further research is necessary to disentangle the multiple behavioural mechanisms explaining why males seem to be more vulnerable to respiratory infections.…”
Section: Discussionsupporting
confidence: 92%
“…Being of a younger age is an important predictor of non-adherence to preventive behaviours [ 27 ]. Frequent communication regarding the SARS-CoV-2 virus stressed the fact that COVID-19 threatens mainly the older population.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the literature in occupational health that often shows that younger workers are more vulnerable because of more precarious employment conditions [ 26 ]. This finding might also be explained in terms of risk perception and adherence to preventive behaviours, which might be lower among younger people, as previously suggested [ 27 ], but should be thoroughly studied. Furthermore, the incidence among other healthcare workers, including medical and other trainees and younger workers with a temporary contract, confirms this cluster of vulnerability during the second wave in comparison with their colleagues.…”
Section: Discussionmentioning
confidence: 63%
“…COVID-19 preventive measures include wearing face masks, hand and cough hygiene, physical distance, and avoiding social gatherings [ 1 ]. In low- and middle-income countries (LMICs), for example, in Brazil in April 2020, hand hygiene was practiced by 98.7% of participants; 92.6% kept physical distancing, 94.2% adhered to cough hygiene, and 45.5% wore face masks [ 2 ], and in two studies in Mozambique in April and June 2020, the prevalence of wearing face masks ranged from 93.9% to 96.5%, likewise physical distancing ranged from 82.2% to 86.7%, regular hand washing 95.4%–96.4%, and covering mouth after coughing/sneezing 96.6%–96.9% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of studies investigating the impact of mental problems on adherence to COVID-19 preventive measures [ 1 ]. A large study in 48 countries found that “the more stressed people felt, the less adherent they were with preventive COVID-19 behavioural guidelines; but also, that more concerned individuals tended to be more adherent with preventive measures.” [ 14 ].…”
Section: Introductionmentioning
confidence: 99%